Comparison of acid versus laser etching on the clinical performance of a fissure sealant: 24-month results - Karaman, E; Yazici, A R; Baseren, M; Gorucu, J (Operative dentistry, 2013)
To compare the clinical performance of a pit and fissure sealant placed with the use of different enamel preparation methods, i.e. acid or Er,Cr:YSGG laser etching, over 24 months. Sixteen subjects (15 female, 1 male) with no restorations or sealant present on their fissures and no detectable caries participated. Using a table of random numbers, a total of 112 sealants (56 with acid-etching, 56 with laser etching) were placed on the permanent premolar and molar teeth. All restorative procedures except for application of the laser were performed by the same dentist. After completion of the fissure preparation either with acid or laser, the adhesive was applied; then a pit and fissure sealant, Clinpro Sealant, was placed and polymerized. Clinical evaluations were done at baseline and at 6-, 12-, 18-, and 24-month follow-up visits by two calibrated examiners, who were unaware of which etching method had been used. The retention of sealants and caries were evaluated with the aid of a dental explorer and an intra-oral mirror. Each sealant was evaluated using the following criteria: 1=completely retained; 2= partial loss; 3= total loss. The Pearson chi-square test was used to evaluate differences in the retention rates among the sealants used with different etching methods. All patients attended the 24-month follow-up visit and all sealants were evaluated (total recall rate 100%). At the end of 24 months, 83.9% of the sealants from laser group and 85.7% of those from acid-etch group were recorded as "completely retained". There were no statistically significant differences in retention rates among the preparation methods after all evaluation periods (p>0.05). No statistically significant differences were found between the retention rates of premolar and molars at each evaluation period. No secondary caries was detected in association with any sealants. The clinical performance of fissure sealants placed after acid or Er,Cr:YSGG laser etching was similar.